(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
An accurate and precise HPLC method was developed for the simultaneous determination of perindopril and amlodipine. The UV range used remains in between 190-380 nm. The instrument used in the genre is known as ultraviolet - Visible spectrophotometer. A molecule absorbs ultra-violet radiation when the energy of such radiation becomes equal to the energy necessary to performing an electronic transaction of the molecule.